2016
DOI: 10.1002/dc.23469
|View full text |Cite
|
Sign up to set email alerts
|

An ancillary method in urine cytology: Nucleolar/nuclear volume ratio for discrimination between benign and malignant urothelial cells

Abstract: This study analyzed the nuclear and nucleolar volume to establish an index for discrimination of benign and malignant urothelial cells, providing possible additional information in urine cytology. Diagn. Cytopathol. 2016;44:483-491. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is generally known that the nuclearcytoplasmic ratio is a very important tool for the cell identification including differentiation or proliferation state. On the other hand, the relationship between the nucleolar and nuclear size was less studied although some previous studies provided useful information on the knowledge of malignant cells already in the last and even in the present century (Foot 1937, McGrew 1965, Busch and Smetana 1970, Tone et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that the nuclearcytoplasmic ratio is a very important tool for the cell identification including differentiation or proliferation state. On the other hand, the relationship between the nucleolar and nuclear size was less studied although some previous studies provided useful information on the knowledge of malignant cells already in the last and even in the present century (Foot 1937, McGrew 1965, Busch and Smetana 1970, Tone et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The overall sensitivity of urine cytology for the diagnosis of UC ranges from 13 to 75%, and a specificity of 85-100% [2]. Urine cytology has relatively high diagnostic specificity for HGUC [10,11], but a low sensitivity in general, especially for LGUC [12]. By definition, tumor cells of LGUC have similar individual cell morphological char-acteristics to normal urothelial cells, which is difficult to distinguish with the human eye.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…On the other hand, in clinical cytology this ratio appeared to be useful for the detection of malignant cells [2][3][4][5]. At this occasion it should be mentioned that the nucleolus : nucleus ratio was usually estimated using the "oculometry" and expressed by diameter, volume or area calculations [6,7]. Recent studies on cultured leukemic granulocytic progenitors indicated that the diameter ratio of nucleolar bodies to nuclear body reflected a remarkable stability of the nuclear space occupied by nucleolar bodies after the treatment with anti-leukemic drugs [8].…”
Section: Introductionmentioning
confidence: 99%